Nodular fasciitis of the face: A case report. (2019) - Al-Hayder, Shems; Warnecke, Mads; Hesselfeldt-Nielsen, Jørgen
Highlights: Nodular fasciitis is a benign self-limited lesion. It is can misdiagnosed as a sarcoma. Local excision is the preferred treatment. Spontaneous regression is common. Recurrence is rare. Abstract: Introduction: Nodular fasciitis is a benign, self-limited myofibroblastic proliferative lesion of unclear aetiology. It is often misdiagnosed as a malignant tumour due to its rapid growth, high cellularity, and increased mitotic activity. Presentation of case: We present a case of nodular fasciitis occurring in the medial canthus of a 64-year-old, otherwise healthy, woman. The patient complained of rapidly enlarging asymptomatic subcutaneous nodule over a period of 6 months. The tumour was firm, smooth, and indolent with limited mobility. Fine-needle aspiration was inconclusive, and the CT scan showed a well-defined nodular lesion in the soft tissue without bone destruction. A local excision was performed, and the histopathological findings were consistent with nodular fasciitis. Discussion: Although rare, nodular fasciitis is the most common pseudosarcoma of soft tissues. Local excision is recommended; however, the tumour often regresses spontaneously, and recurrence is exceedingly rare. Conclusion: Awareness of nodular fasciitis and its benign nature is essential to avoid misdiagnosis and subsequent inappropriate aggressive treatment of the patient.